Effect of Volume Fraction Filler on Sound Insulation in Oil Palm Fronds Fiber Composite Polyester Matrix - Sidiq, Firman; Sulistijono, Sulistijono; Ismail, Ika (IPTEK Journal of Proceedings Series, 2018)
In this study, the effect of adding palm fiber rods to the polyester matrix for sound insulation purposes was investigated. The type of fiber used is short fibers with random orientation with the percentage difference in the amount of fiber in the composite as a comparison. Testing loss of voice transmission using impedance tube method is done to know the ability of material to reduce or prevent sound. The data obtained from the TL test results were analyzed and the STC (sound transmission class) values were calculated on each sample. The best results obtained are in the first and second samples with the percentage of fiber 0% and fiber 30%. The calculated results of the STC values in samples one and two each have 32.1 dB and 31.6 dB which indicates sufficient ability to defeat the loud noise. Based on these results, a composite with a 30% fiber content can be used as a sound insulation material and can reduce waste of palm oil that is underutilized.